Career Adaptability of Madrasah Ibtidaiyah Teacher Education Students: Problems and Alternative Development - Rina Rindanah; A. Juntika Nurihsan; Uman Suherman; Amin Budiamin (Al Ibtida: Jurnal Pendidikan Guru MI, 2021)
AbstractThe goal of this study is to describe the career adaptability profile of the Madrasah Ibtidaiyah Teacher Education students, as well as their developmental issues and alternatives. This is a quantitative study with a population of all the Madrasah Ibtidaiyah Teacher Education students at one of Cirebon City's universities, and a sample size of 70 individuals. Questionnaires and interview guides were utilized as research tools. The research data was then examined utilizing descriptive-analytic approaches, both quantitative and qualitative. The results revealed that the students of the Madrasah Ibtidaiyah Teacher Education had a modest career adaptability score, with a percentage of 47.14 percent. In terms of gender, female students' average career adaptability score was greater than male students' average career adaptability score. Elements of career concern, career curiosity, career self-control, and elements of career contribution are all positive aspects of career adaptability. However, there is still room for improvement in terms of career self-confidence, career collaboration, and professional continuity. Conducting mentorship programs for students in preparing career plans, determining and selecting careers, enhancing the role of academic supervisors, and establishing a student career development center are all options for improving student careers.Keywords: career adaptability, alternative career development, students.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan secara komprehensif profil adaptabilitas karir mahasiswa Pendidikan Guru Madrasah Ibtidaiyah beserta masalah dan alternatif pengembangannya. Penelitian ini merupakan penelitian kuantitatif dengan populasi seluruh mahasiswa Pendidikan Guru Madrasah Ibtidaiyah di salah satu perguruan tinggi di Kota Cirebon dan sampelnya berjumlah 70 mahasiswa. Instrumen penelitian yang digunakan berupa angket dan pedoman wawancara. Data hasil penelitian kemudian dianalisis menggunakan teknik analisis deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa skor rata-rata adaptabilitas karir mahasiswa Pendidikan Guru Madrasah Ibtidaiyah tergolong sedang, dengan persentase sebesar 47.14%. Ditinjau dari jenis kelamin, skor rata-rata adaptabilitas karir mahasiswa perempuan lebih tinggi dibandingkan skor rata-rata adaptabilitas karir mahasiswa laki-laki. Dari tujuh aspek adaptabilitas karir, aspek kepedulian karir, keingintahuan terhadap karir, pengendalian diri terhadap karir dan aspek kontribusi dalam karir sudah baik. Namun demikian, pada aspek keyakinan diri terhadap karir, kerjasama dalam membangun karir dan keberlanjutan karir masih harus ditingkatkan. Alternatif yang dapat dilakukan dalam mengembangkan karir mahasiswa adalah dengan melakukan program pendampingan kepada mahasiswa dalam menyusun rencana karir, penetapan dan pemilihan karir, peningkatan peran dosen pembimbing akademik, serta pendirian pusat pengembangan karir mahasiswa.Kata kunci: adaptabilitas karir, alternatif pengembangan karir, mahasiswa.